Analysis and comprehensive assessment method of power quality in advanced distribution networks based on complex network theory - Zheng, Jieyun; Chen, Ruochen; Zhang, Zhanghuang; Wei, Xin; Xue, Jingwei (Frontiers in Energy Research, 2024)
As China continues to develop the advanced power systems, the network structure of distribution networks is becoming increasingly complex. The integration of numerous power electronic devices has caused growing severity of power quality issues in present-day distribution networks. Moreover, the complexity of the networks has resulted in a significant increase in the volume of power quality data, posing greater challenges in data processing and power quality assessment. In addressing this issue, this paper investigates a novel method for comprehensive assessment of power quality in advanced distribution networks (ADN) grounded in complex network theory. First, the influencing factors of power quality in advanced distribution networks are analyzed, and based on this analysis, the power quality evaluation indicators for advanced distribution networks are determined. Then a node characteristic matrix of the distribution network is constructed based on complex network theory which is used to generate the significance of each node within the network. Moreover, the sequential relationship analysis method (G1) and criteria importance though intercrieria correlation (CRITIC) method are leveraged to determine the subjective and objective weights of each indicator. These weights are then combined to calculate the comprehensive weight, which is further optimized using a two-stage method to increase the rationality. Furthermore, a fuzzy comprehensive evaluation method is applied to quantitatively assess the power quality within ADN. Finally, the proposed method is validated using measurement data from a specific ADN. The findings demonstrate the rationality and effectiveness of the proposed method, providing valuable insights for optimizing power quality of advanced distribution systems.